In vitro Characterization of Insulin−Producing β-Cell Spheroids - Ntamo, Yonela; Samodien, Ebrahim; Burger, Joleen; Muller, Nolan; Muller, Christo J. F.; Chellan, Nireshni (Frontiers in Cell and Developmental Biology, 2021)
Over the years, immortalized rodent β-cell lines such as RIN, HIT, MIN, βTC and INS-1 have been used to investigate pancreatic β-cell physiology using conventional two-dimensional (2D) culture techniques. However, physical and physiological limitations inherent to 2D cell culture necessitates confirmatory follow up studies using sentient animals. Three-dimensional (3D) culture models are gaining popularity for their recapitulation of key features of in vivo organ physiology, and thus could pose as potential surrogates for animal experiments. In this study, we aimed to develop and characterize a rat insulinoma INS-1 3D spheroid model to compare with 2D monolayers of the same cell line. Ultrastructural verification was done by transmission electron microscopy and toluidine blue staining, which showed that both 2D monolayers and 3D spheroids contained highly granulated cells with ultrastructural features synonymous with mature pancreatic β-cells, with increased prominence of these features observed in 3D spheroids. Viability, as assessed by cellular ATP quantification, size profiling and glucose utilization, showed that our spheroids remained viable for the experimental period of 30 days, compared to the limiting 5-day passage period of INS-1 monolayers. In fact, increasing ATP content together with spheroid size was observed over time, without adverse changes in glucose utilization. Additionally, β-cell function, assessed by determining insulin and amylin secretion, showed that the 3D spheroids retained glucose sensing and insulin secretory capability, that was more acute when compared to 2D monolayer cultures. Thus, we were able to successfully demonstrate that our in vitro INS-1 β-cell 3D spheroid model exhibits in vivo tissue-like structural features with extended viability and lifespan. This offers enhanced predictive capacity of the model in the study of metabolic disease, β-cell pathophysiology and the potential treatment thereof.